Didactical Design to Complete the Story Questions on FPB in Elementary School - Rohayani, Ai Yani; Herman, Tatang (International Conference on Elementary Education, 2020)
The aim of this research is improve students' skills in completing story question of mathemathics in the concept of the greatest common divisor (FPB) in sixth grade students in one of elementary school in Ibun, Bandung with the sample of the research are 38 students. The research method uses didactical design research (DDR). Techniques data collection used the instruments were written questions and interviews. The didactic design that is used for the greatest common factor (FPB) lesson is started from the discovery of problems in learning that is the students are difficult to complete the story questions, and then it is arranged the way to complete the story questions in the form of the Bar Model and designed alternative responses from students so that a learning design is gotten to improve student skills in completing story questions. While student activities in the learning is begun from understanding the story questions with indicators that is students can visualize in the form of bar models. The results show that the didactical design that has done be able to improve students' skills in completing story questions on FPB lesson in sixth grade so that the learning become more optimal